EFIKASI SUPLEMEN BESI-MULTIVITAMIN UNTUK PERBAIKAN STATUS BESI REMAJA WANITA - Dodik Briawan; Hardinsyah .; Muhilal .; Budi Setiawan; Sri Anna Marliyati (PERSATUAN AHLI GIZI INDONESIA, 2007)
EFFICACY OF IRON-MULTIVITAMIN SUPPLEMENT FOR IMPROVING THE IRON STATUS OF ADOLESCENT FEMALESThe study was aimed to analyze the efficacy of supplementation iron-multivitamin for improvingthe iron status of adolescent females through the double-blind trial. Subjects were 224 of the firstgrade university students (IPB) who were randomly allocated to three study groups through adouble blind trial. The first group received only placebo (control group); the second group received60 mg iron, 250 ug folate (B-F group); the third group received 60 mg iron,800 ug folate, 4200 ugretinyl acetate, 500 mg vitamin C, and 16.8 ug vitamin B12 (B-MV group). All supplements weredistributed and consumed weekly during 25 weeks. The mean changes in Hb, STfR and SFamong the groups were tested with Ancova and adjusted with BMI; capsule compliance;food/snack compliance; adequacy of energy, protein, vitamin A, vitamin C, iron; and baselinevalue of Hb, STfR, SF. The results showed the demographics and nutritional characteristics ofsamples were not significantly different. At the baseline, the mean of haemoglobin(Hb=126.2±13.1 g/l) and serum ferritin (SF=18.3±15.9 ug/l) were not significantly different amongthe three groups (p0.05). However, the serum transferrin receptor (STfR) was lower in the control(5.8 ± 3.2 mg/l) than B-F (7.9 ±4.4 mg/l) and B-MV (11.8±5.5 mg/l). After 25 week ofsupplementation, the mean change of hemoglobin was not different among the three groups (10.1g/l; p0.05). The B-MV group significantly lower decreased in STfR (-4.2 mg/l) and higherincreased in SF (+13.4 ug/l) compared to B-F and control group (p0.05). Meanwhile, only theSTfR in B-F group (-1.3 ug/l) was significantly lower than control group (p0.05). This implied theimportant of the multi-vitamin to complement the iron supplementation.Keywords: haemoglobin (Hb), serum transferrin receptor (STfR), serum ferritin (SF), iron status, iron-multivitamin, iron-folate, adolescent female